'Genuine' refugees or illegitimate 'boat people': Political constructions of asylum seekers and refugees in the Malaysia Deal debate. Issue 2 (July 2014) - Rowe, Elizabeth; O'Brien, Erin
Abstract : Immigration to Australia has long been the focus of negative political interest. In recent times, the proposal of exclusionary policies such as the Malaysia Deal in 2011 has fuelled further debate. In these debates, Federal politicians often describe asylum seekers and refugees as 'illegal', 'queue jumpers', and 'boat people'. This article examines the political construction of asylum seekers and refugees during debates surrounding the Malaysia Deal in the Federal Parliament of Australia. Hansard parliamentary debates were analysed to identify the underlying themes and constructions that permeate political discourse about asylum seekers and refugees. We argue that asylum seekers arriving in Australia by boat were constructed as threatening to Australia's national identity and border security, and were labelled as 'illegitimate'. A dichotomous characterisation of legitimacy pervades the discourse about asylum seekers, with this group constructed either as legitimate humanitarian refugees or as illegitimate 'boat arrivals'. Parliamentarians apply the label of legitimacy based on implicit criteria concerning the mode of arrival of asylum seekers, their respect for the so‐called 'queue', and their ability to pay to travel to Australia. These constructions result in the misrepresentation of asylum seekers as illegitimate, undermining their right to protection under Australia's laws and international obligations.